Transformative learning model for IIUM undergraduates: a framework to foster knowledge generation through reflective writing style - Eid, Iyad Muhammad; Rahman, Shukran Abdul; Md. Noon, Hazizan; Rokis, Rohaiza (Al Manar Resources, 2025)
Objective: This writing aims to design a guiding framework that enables undergraduate students studying at the International Islamic University Malaysia (IIUM) to excel in reflective writing assignments. The proposed model also offers significant benefits to IIUM lecturers, who can adapt it to suit their teaching subjects, ultimately leading to enhanced reflective writing competencies among their students. Methodology: This framework has been formulated through a combination of extensive teaching experience in higher education and empirical investigations focused on undergraduate and postgraduate learners. The model was developed through the contributions of thirty undergraduate students enrolled in three academic subjects offered by the Department of Sociology and Anthropology (SOCA): Sociological and Anthropological Theory I, Social Demography and Population Transformation, and Sociology of the Cyberspace. The cohort for this model mainly features local Malay undergraduates from SOCA, along with two international students and three students from the English and psychology departments. All participants were enrolled in the three learning subjects during the first semester of the 2024-2025 academic year. Results: Implementing the framework model with undergraduate students demonstrates their ability to actively collaborate in generating valuable knowledge, fulfilling three essential objectives: (1) Students showcase authentic writing skills based on their comprehensive grasp of the subjects without relying on AI or other online sources; (2) The model can serve as a guideline to help newly enrolled students understand the scope of the subjects through their peers’ experience, even before registering their subjects, and (3) the model provides a structured approach to encourage lecturers to develop their discipline-specific guidelines, supporting new students with the content of the subjects, which will be a novel experience in academia introduced by IIUM.